Weight loss increases all-cause mortality in overweight or obese patients with diabetes: A meta-analysis. Issue 35 (August 2018) - Chen, Yiqi; Yang, Xue; Wang, Juyang; Li, Yangshiyu; Ying, Dou; Yuan, Huijuan
Abstract: Background: Overweight and obese patients with diabetes are advised to lose weight to improve their health; however, recent studies have demonstrated that weight loss may be associated with worse long-term survival in patients with diabetes. This meta-analysis aimed to examine the relationships between weight loss and all-cause mortality in overweight or obese individuals with diabetes. Methods: We searched the PubMed and EMBASE databases from inception to February 2017. We included prospective studies that reported sufficient information to extract mortality-specific relative risks (RRs) with corresponding 95% confidence intervals (CIs). RRs with 95% CIs were pooled using a random-effects model. A subgroup analysis was also performed to explore sources of heterogeneity. Results: Of the 1652 studies identified, 8 met the inclusion criteria. A total of 18, 887 patients were included in this analysis. We found that compared with a stable weight, weight loss was associated with an increased risk of all-cause mortality (RR, 1.15; 95% CI, 1.04 to 1.28) and cardiovascular disease (CVD) mortality (RR, 1.15; 95% CI, 1.02 to 1.29) in overweight or obese adults with diabetes, whereas intentional weight loss was not associated with changes in all-cause mortality (RR, 0.90; 95% CI, 0.67 to 1.22). Weight gain was not associated with changes in all-cause mortality (RR, 1.17; 95% CI, 0.87 to 1.58) or CVD mortality (RR, 0.97; 95% CI, 0.93 to 1.01). Compared with an initial body mass index (BMI) of 25 to 30 kg/m 2, an initial BMI of >35 kg/m 2 was associated with increased all-cause mortality (RR, 1.23; 95% CI, 1.01 to 1.50), which was further increased with an initial BMI of >40 kg/m 2 (RR, 1.50; 95% CI, 1.16 to 1.94). Conclusion: Our results indicate that weight loss but not weight gain increased all-cause mortality and CVD mortality in overweight or obese adults with diabetes. Abstract : Supplemental Digital Content is available in the text